Present-day mass loss rates are a precursor for West Antarctic Ice Sheet collapse - T. van den Akker; W. H. Lipscomb; G. R. Leguy; J. Bernales; C. J. Berends; W. J. van de Berg; R. S. W. van de Wal; R. S. W. van de Wal (The Cryosphere)
Observations of recent mass loss rates of the West Antarctic Ice Sheet (WAIS) raise concerns about its stability since a collapse would increase global sea levels by several meters. Future projections of these mass loss trends are often estimated using numerical ice sheet models, and recent studies have highlighted the need for models to be benchmarked against present-day observed mass change rates. Here, we present an improved initialization method that optimizes local agreement not only with observations of ice thickness and surface velocity but also with satellite-based estimates of mass change rates. This is achieved by a combination of tuned thermal forcing under the floating ice shelves and friction under the ice sheet. Starting from this improved present-day state, we generate an ensemble of future simulations of Antarctic mass change by varying model physical choices and parameter values while fixing the climate forcing at present-day values. The dynamical response shows slow grounding-line retreat over several centuries, followed by a phase of rapid mass loss over about 200 years with a consistent rate of ∼3 mm GMSL yr−1 (global mean sea level). We find that, for all ensemble members, the Thwaites Glacier and Pine Island Glacier collapse. Our results imply that present-day ocean thermal forcing, if held constant over multiple centuries, may be sufficient to deglaciate large parts of the WAIS, raising global mean sea level by at least a meter.